From paddy fields to sustainable town in four decades: tight integration of urban planning and place management in Yukarigaoka, Japan - Capitanio, Marco; Sintusingha, Sidh (Journal of Architecture and Urbanism, 2021)
Private real estate developers disproportionately focus on spatial planning and short-term returns, often forgetting the crucial role played by place management toward the achievement of sustainable communities. This research presents an alternative model of privately initiated urban development: Yukarigaoka, a new town in the eastern outskirts of Tokyo founded in the late 1970s. The case study has been analyzed through field research, assessments of local media, interviews and literature review, focusing on urban planning strategies and place management practices. Yukarigaoka is a non-speculative model entailing the developer’s long-term commitment to the creation of a community sustained by unique planning features and innovative, award-winning place management practices. As a result, the development avoided the demographic imbalance of many Japanese public new towns of the same period. Population has been constantly growing and the town has been attracting families, strengthening local engagement and a defined identity. Despite a degree of paternalism in approach and the mediocre design quality of the built environment, Yukarigaoka confirms that livable communities result from the tight integration of planning and management. It provides an important planning and management precedent for new and existing communities in other Asia-Pacific cities toward establishing a synergistic relationship between built and natural components and in advocating for long-term profit different from a predominantly neoliberal developmental model that maximizes immediate returns.